1983
DOI: 10.1152/jappl.1983.55.4.1349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical training on myocardial enzyme activities in aging rats

Abstract: Male Fischer rats of four age groups were subjected to a 3-mo exercise training program that consisted of a gradual increase to 1 h/day of forced swimming. Exercise was initiated at 1, 6, 12, or 17-22 mo of age. After the training period there was an increase in the heart weight relative to body weight in all groups, but heart weight was increased only in the two oldest groups. The specific activities of both actomyosin ATPase and creatine kinase isolated from cardiac muscle decreased with age. In animals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The above observations supported the concept put forward by Edington and coworkers that for a certain intensity and duration of exercise there is a threshold of age beyond which exercise may be deleterious to the aging animals (74). Similar observations of a threshold of age prevailing for myocardial ATPase and creatine kinase activities were reported by Chesky et al (75). More recent studies by Holloszy and Smith have shown that rats exercised regularly from very young age indeed have had a longer mean life span than their counterpart sedentary controls (76).…”
Section: The Influence Of External Conditions and Environmental Factorssupporting
confidence: 89%
“…The above observations supported the concept put forward by Edington and coworkers that for a certain intensity and duration of exercise there is a threshold of age beyond which exercise may be deleterious to the aging animals (74). Similar observations of a threshold of age prevailing for myocardial ATPase and creatine kinase activities were reported by Chesky et al (75). More recent studies by Holloszy and Smith have shown that rats exercised regularly from very young age indeed have had a longer mean life span than their counterpart sedentary controls (76).…”
Section: The Influence Of External Conditions and Environmental Factorssupporting
confidence: 89%
“…The present and previous data [2,3,5,[7][8][9][12][13][14] lead us to conclude that the capacity to adapt to physical exercise in skeletal muscle, heart muscle and bone tis sue is probably maintained as long as the training program has started prior to a cer tain threshold of age, which is at least 15 months in mice (e.g. the result depicted in figure 4).…”
Section: Discussionsupporting
confidence: 69%
“…As the euthyroid rat matures, the percent of V, decreases while the percent of V 3 increases, l8 - 25 - 28 and this shift is accompanied by a decrease in the ATPase acby guest on May 10, 2018 http://circres.ahajournals.org/ Downloaded from tivities in a variety of myofilament preparations. 29 " 31 With further adult aging into senescence, the ATPase activity in some but not all myofilament preparations continues to decline 2930 - 32 and the contraction duration becomes prolonged.…”
mentioning
confidence: 99%